REBRANDING KEBUN BINATANG SURABAYA DENGAN MENGGUNAKAN KARAKTERISTIK BERBASIS BUDAYA LOKAL - Andriani, Dewi Restya; Bahruddin, Muh; Dewanto, Thomas Hanandry (Jurnal Art Nouveau, 2017)
conducted using qualitative research methods, namely by doing interviews, observation, documentation, library and study to get the data used as the supporter of the creation of the concept design of rebranding. The data were analyzed by using multiple stages, namely the reduction of the data, the presentation of data and conclusions. rom the analysis of the data found few keyword refers to the communication strategy rebranding which will be used to achieve the intended targets of the audians. After analysis of the data, the concept of virtue or keyword design of rebranding of "Smart". The description of the concept is smart thinking and the nature of the child that shows intelligence. The concept of "Smart" aims to show that the Zoo in Surabaya was the tour has the identity pndidikan, ex-situ, research and recreation. The concept of smart aims to convey the identity of Surabaya Zoo to the tourists to pay a visit to the place that is capable of offering entertainment and education for children. The result of the design of rebranding is to preserve the local culture. Keywords: Rebranding, Surabaya Zoo, Local Culture